Achieve distributed and secure Internet of things structure using multi-chains solution of blockchain technology: تحقيق بنى موزعة وآمنة لانترت الأشياء عبر السلاسل المتعددة لتقنية البلوكتشين - Sara Mostafa Soleman (Journal of engineering sciences and information technology, 2021)
The Internet of Things (IoT) is considered a high-impact technology in many major markets. It promises many opportunities, but there are several risks and drawbacks associated with this technology stand in the way of realizing its potential opportunities, such as the IoT devices limited capabilities (restricted resources) as well as the current access control systems based on central structures and central hierarchies. with all IoT devices, the security risks and threats are enormous. Blockchain is defined as tamper-proof, tamper-resistant digital ledgers that are executed in a distributed fashion, i.e., without a central repository and usually without central authority, allowing all parties to track information over an insecure network without the need for third-party verification. This technology could be a solution to the problems facing the Internet of Things, however the integrating between blockchain and Internet of Things system comes with many challenges as such blockchain suffers from high resource consumption, slow response, etc. In this research we will propose a new architecture for how to integrate blockchain with the Internet of Things. This structure consists of the smart home responsible for its own data (own chain) and the service provider which considered indirect manager of the network. The performance of the proposed architecture will be studied in terms of expansion, decentralization, security and permanent availability.